Amtsal Al-Qur’an dalam Perspektif Kurikulum Pendidikan Agama Islam - Mas’ud, Moh. Ali (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2020)
The development and progress of education in Indonesia is very significant, starting from the education implementation system, education content, curriculum, learning methods, facilities, and infrastructure in education. Al-Quran has provided instructions regarding how and what education is like, including the issue of amtsal. Weaknesses in conducting a study of the main sources of Islamic law have resulted in a lack of research on the contents of the Qur'an, especially those related to education. al-Qur'an contains content that answers various problems of life so that exploration of the Koran must be encouraged and improved. This article uses a qualitative method with the type of library research. From the studies that have been done, it can be concluded that the objective: the purpose in the proverbs or the purpose of making the proverbs in the al-Qur'an is for people to think. This does not conflict with the goals of education, where the purpose of education is so that humans can think and become adults. Material: in Proverbs al-Qur'an, the existing materials include materials commonly taught in Islamic religious education, namely: the fields of faith, morals, worship, history, and science. Method: in this case, we can note that the method used is by explaining or expressing abstract things to be concrete by likening the properties contained in abstract things with the properties that are already known. general. Media: in paralleling this abstract matter, the Proverbs of the Qur'an uses a very real medium that we see every day, namely the universal medium (the universe). Evaluation: in this Proverbs al-Qur'an the writer does not find evaluation elements as well as components of the educational curriculum to assess the success that he has attempted.